Innovation in underground mining in reducing rockfall accidents through technological and sustainable solutions - Agreda Angulo, Nicolle Elizabeth; Aquino Robles, Carlitos David; Laiza Vera, Walter Klysman; Minaya Masias, Manuel Alejandro (LACCEI, 2025)
Underground mining is one of the most complex and hazardous working environments due to the natural instability of the terrain and variable geological conditions. In this context, rockfalls remain a leading cause of fatal accidents. Despite advancements, 50% of mining-related deaths in 2024 were due to rockfalls, according to Fernando Borja, Director of the Mining Safety Institute (ISEM), underscoring the urgent need to improve support systems in underground operations. This study aims to identify the most appropriate support type based on the characteristics of the rock mass, including strength, degree of fracturing, and geomechanical conditions, using classification tools such as GSI, RMR, and the Q-System. Beyond traditional support analysis, the integration of technological and sustainable innovations is proposed. These include instrumented bolts with FBG sensors for real-time monitoring of deformations, and eco-friendly shotcrete incorporating recycled additives to reduce environmental impact. Together, these solutions seek to enhance the safety and efficiency of underground operations, offering a technical approach that ensures structural stability while prioritizing worker protection. The proposal reinforces a commitment to safe, modern, and socially responsible mining engineering practices that align with current demands for sustainability and risk reduction in the mining sector.